PERBANDINGAN KONSEP KEPRIBADIAN MENURUT BARAT DAN ISLAM - Agus Silahudin (AL-FIKRA, 2018)
Personality is something that attracts the attention of many parties. Many theories that try to give some concepts and definitions related to the human personality with different points of view. Western psychologists try to provide a definition of personality that is psychological based on the word person, but until now the personality psychologists themselves still do not agree on what the definition of personality actually is. While in Islam, the concept of personality has been thoroughly discussed in various Islamic literature. The Apostle as an example for Muslims has applied the concept of personality and actions and behavior. Thus, the concept of personality according to Islam, that Islamic personality is defined as "a unified integration of the workings of aqliyah and nafsiyah based on Islamic faith which gives birth to actions". Human personality is not shaped and influenced by body shape, face and other accessories. Human personality is formed by aqliyah and nafsiyah.